2019
DOI: 10.1016/j.cell.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Physical Principles of Membrane Shape Regulation by the Glycocalyx

Abstract: Cells bend their plasma membranes into highly curved forms to interact with the local environment, but how shape generation is regulated is not fully resolved. Here, we report a synergy between shape-generating processes in the cell interior and the external organization and composition of the cell-surface glycocalyx. Mucin biopolymers and long-chain polysaccharides within the glycocalyx can generate entropic forces that favor or disfavor the projection of spherical and finger-like extensions from the cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
249
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(257 citation statements)
references
References 117 publications
7
249
0
1
Order By: Relevance
“…These results suggested that the corolla pattern formation can also be driven by a phase separation process with competition for space between a percolating phase enriched in CD45 and microdomains enriched in CD2-CD58. Other glycocalyx components could contribute to corolla formation (42).…”
Section: Glycocalyx Proteins Residing In the Dsmac Promote Corolla Pamentioning
confidence: 99%
“…These results suggested that the corolla pattern formation can also be driven by a phase separation process with competition for space between a percolating phase enriched in CD45 and microdomains enriched in CD2-CD58. Other glycocalyx components could contribute to corolla formation (42).…”
Section: Glycocalyx Proteins Residing In the Dsmac Promote Corolla Pamentioning
confidence: 99%
“…Since peaks of ecdysone-controlled Tnc (Fraichard et al, 2006) coincide with formation of new boutons, Tnc may play a major role in the restructuring of the synaptic structures. Mucins appear to be particularly effective at bending cell membranes (Shurer et al, 2019). At synaptic terminals, this cell behavior may facilitate formation of round boutons, with minimal cell surface, thus concentrating the AZ components.…”
Section: Discussionmentioning
confidence: 99%
“…Cell membrane (plasma membrane) and nuclear membrane are lipid bilayers that are dotted with various protein complexes and ion channels that allow for the transmigration of molecules. In a coarse-grained scenario, the cell membrane can be considered to be composed of a combination of a lipid bilayer, glycocalyx (polymer chains of glycolipids and glycoproteins [46]) and the actin cytoskeleton meshwork attached to the lipid bilayer. This composite cell membrane behaves as a viscoelastic material that ows like a viscous liquid over a short time duration but exhibits a solid-like elastic behaviour at suciently long timescales.…”
Section: Viscoelasticity Of Cell and Extracellular Matrix (Ecm)mentioning
confidence: 99%